Effect of Intra-Testicular Administration of Clove Oil on Testicular Morphometry in Dogs - Kumar, Jitendra; Shukla, Satya Nidhi; Chouksey, Shivika (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present work was designed to study the effect of intra-testicular administration of clove oil solution on testicular morphometry. Thirty sexually mature adult male dogs were taken and randomly divided into 5 groups comprising six animals in each. The animals were administered intratesticular injection of clove oil (G-I), clove oil along with lignocaine (G-II), clove oil with olive oil (G-III) and eugenol (G-IV) once @ 1.0 mL in each group. The testicular morphometry in terms of size (length, width, thickness); testicular circumference and paired volume of intact testes was determined. The testicular size was increased on day 7 as compared to day 0 and then decreased gradually from day 7 to day 45 in clove oil, clove oil along with lignocaine, clove oil with olive oil and eugenol administered groups. The reduction in mean paired volume of testes (PVT) at day 45 was highest in G-II (35.74 %) followed by G-IV (26.57%), G-I (26.22 %), Group-III (25.19 %) and G-V (0.12 %). Mean decrease in scrotal circumference at day 45 was highest in G-II (8.14 %) followed by G-IV (7.64 %), G-I (5.91 %), G-III (3.66%) and G-V (0.29 %). These findings were also supported by semen quality evaluated in selected few animals. The study revealed that intratesticular administration of clove oil along with lignocaine and eugenol separately reduced testicular size which may be attributed due to degenerative changes in the testicles.